Consistent differences in foraging behavior in 2 sympatric harvester ant species may facilitate coexistence. Issue 5 (12th September 2017) - Saar, Maya; Subach, Aziz; Reato, Illan; Liber, Tal; Pruitt, Jonathan N; Scharf, Inon
Abstract: The co-occurrence of 2 similar species depends on their ability to occupy different ecological niches. Here, we compared the consistency of different aspects of foraging behavior in 2 co-occurring harvester ant species ( Messor ebeninus and Messor arenarius ), under field conditions. The 2 species are active concomitantly and display a similar diet, but M. arenarius features smaller colonies, larger workers on average, and a broader range of foraging strategies than M. ebeninus . We characterized the flora in the 2 species' natural habitat, and detected a nesting preference by M. arenarius for more open, vegetation-free microhabitats than those preferred by M. ebeninus . Next, we tested the food preference of foraging colonies by presenting 3 non-native seed types. Messor arenarius was more selective in its food choice. Colonies were then offered 1 type of seeds over 3 days in different spatial arrangements from the nest entrance (e.g., a seed plate close to the nest entrance, a seed plate blocked by an obstacle, or 3 plates placed at increasing distances from the nest entrance). While both species were consistent in their foraging behavior, expressed as seed collection, under different treatments over time, M. ebeninus was more consistent than M. arenarius . These differences between the species may be explained by their different colony size, worker size, and range of foraging strategies, among other factors. We suggest that the differences in foraging, such as in food preference and behavioral consistency while foraging, could contribute to the co-occurrence of these 2 species in a similar habitat.